Índice de masa corporal elevado como factor de riesgo para fibromatosis uterina en pacientes del Hospital Belén de Trujillo - Pérez Quispe, Ghilardi Pollet (2019)
Introduction: Uterine leiomyomas (fibroids or myomas) are the most common non-cancerous pelvic tumor in women that arise from smooth muscle cells and fibroblasts in the myometrium. Among the risk factors are black race, parity, early menarche, high mci, etc. Objective: To determine if the high body mass index (BMI) is a risk factor for uterine fibromatosis in patients of the Hospital Belén de Trujillo (HBT) during the period 2015 – 2018. Materials and methods: Corresponds to an analytical, observational, retrospective study of cases and controls, where 178 clinical histories were reviewed, where the group of patients selected with uterine myomatosis was 78 (cases) and the group without uterine myomatosis was 78 ( controls). For the statistical analysis, the Chi Square test and the Odds Ratio (OR) were used with a 95% confidence interval (95% CI). Conclusion: The high body mass index is a risk factor for uterine fibromatosis in patients of the Hospital Belén de Trujillo during the period 2015 - 2018.